The Personal Patient Profile-Prostate, Decision Support for Men With Localized Prostate Cancer: A Multi-center Randomized Trial - Berry, Donna L (2011)
OBJECTIVE: The purpose of this trial was to compare usual patient education plus the Internet-based, Personal Patient Profile-Prostate, versus usual education alone, on conflict associated with decision making, plus explore time-to-treatment and treatment choice. METHODS: A randomized, multi-center clinical trial was conducted with measures at baseline, one and six months. Men with newly diagnosed localized prostate cancer who sought consultation at urology, radiation oncology or multi-disciplinary clinics in four geographically-distinct American cities were recruited. Intervention group participants used the Personal Patient Profile-Prostate, a decision support system comprised of customized text and video coaching regarding potential outcomes, influential factors, and communication with care providers. The primary outcome, patient-reported decisional conflict, was evaluated over time using Generalized Estimating Equations to fit generalized linear models. Additional outcomes, time-to-treatment, treatment choice and program acceptability/usefulness, were explored. RESULTS: A total of 494 eligible men were randomized (266 intervention; 228 control). The intervention reduced adjusted decisional conflict over time as compared with the control group, for the uncertainty score (estimate −3.61; (confidence interval, −7.01,−0.22) and values clarity (estimate −3.57; confidence interval (−5.85,−1.30) Borderline effect was seen for the total decisional conflict score (estimate −1.75; confidence interval (−3.61,0.11). Time-to-treatment was comparable between groups, while undecided men in the intervention group chose brachytherapy more often than in the control group. Acceptability and usefulness were highly rated. CONCLUSION: The Personal Patient Profile-Prostate is the first intervention to significantly reduce decisional conflict in a multi-center trial of American men with newly diagnosed localized prostate cancer. Our findings support efficacy of P3P for addressing decision uncertainty and facilitating patient selection of a prostate cancer treatment that is consistent with the patient values and preferences.